Toni Morrison : Memory and Meaning - Tally, Justine; Seward, Adrienne Lanier, 1945- (Book collections on Project MUSE., 2014)
"Toni Morrison: Memory and Meaning boasts essays by well-known international scholars focusing on the author's literary production and including her very latest works--the theatrical production Desdemona and her tenth and latest novel, Home. These original contributions are among the first scholarly analyses of these latest additions to her oeuvre and make the volume a valuable addition to potential readers and teachers eager to understand the position of Desdemona and Home within the wider scope of Morrison's career. Indeed, in Home, we find a reworking of many of the tropes and themes that run throughout Morrison's fiction, prompting the editors to organize the essays as they relate to themes prevalent in Home. In many ways, Morrison has actually initiated paradigm shifts that permeate the essays. They consistently reflect, in approach and interpretation, the revolutionary change in the study of American literature presented by Morrison's focus on the interior lives of enslaved Africans. This collection assumes black subjectivity, rather than argues for it, in order to reread and revise the horror of slavery and its consequences into our time. The analyses presented in this volume also attest to the broad range of interdisciplinary specializations and interests in novels that have now become classics in world literature. The essays are divided into five sections, each entitled with a direct quotation from Home, and framed by two poems: Rita Dove's "The Buckeye" and Sonia Sanchez's "Aaayeee Babo, Aaayeee Babo, Aaayeee Babo.""--